A comparative study to determine the native eye lens protein in the some types of Iraqi vertebrates (Baghdad Science Journal, 2025)
This study showed that the lens in baloot muluki fish Chondrostoma regium is transparent, spherical shape, and solid in textures, while in the tree frog Hyla arborea savignyi, freshwater turtles Clemmys caspia caspia, white–eared bulbul Pycnonotus leucotis and brown rat Rattus norvegicus are transparent, soft and biconvex, it is very soft in white–eared bulbul. There are many significant differences have been recorded between the average weight lens and the total concentration of the protein in the lens all studied animals. Electrical migration process for lens proteins showed that there is one bundle of crystalline –? and one bundle also crystalline–? in all studied species, either crystalline–? may represent one bundle characterized the lens proteins in baloot muluki fish, tree frog, freshwater turtles, and brown rat, while one bundle from crystalline–? appeared in lens proteins of the white – eared bulbul.